A democratic criterion for definitional statehood in international law - Wade Strug, Jonathan (Centre for Law and Society, 2026)
Legal criteria for state creation in international law have always been controversial.9 In addition to suggestions the topic is simply too political for legal regulation,10 there is no consensus concerning what type of criteria are appropriate,11 what the specific criteria should be, 12 how potential criteria should be interpreted, 13 and what role recognition plays in state creation.